Problem Jual Beli Tanah Berstatus Letter C Studi Kasus di Kecamatan Slogohimo Kabupaten Wonogiri - Perwira, Egga Anggara, Darsono, S.H., M.Hum (2016)
The existence Letter C is used by some people as evidence of his land ownership, there is only an evidence of tax payment on customary land, or proof that the land has been registered as an object of taxation and thus should be paid tax. In the context of juridical, legal status of the land is only used other documents as proof of land ownership becomes stronger, because it is not accommodated by the Agrarian Law in force. Status of land which has the force of law Letter C often trigger disputes (potential dispute) because it often happens that someone who controls or work on the land, but the certificate of the right to their land in the name of another person, lands that have not registered their ownership rights, or has not been certified, have a legal risk and higher vulnerability. Therefore, the object of the sale and purchase of land rights that have not registered or have not been certified emphasizes foresight and prudence, so clear and bright as the seller is legitimate and has the right to sell.